Factors Associated with Nurses’ Early Warning System (EWS) Scoring Accuracy and Patient Clinical Outcomes - Aghata Christie Jelita Angkouw; Sabina Gero; Amrih Widiati; Eko Winarto (An Idea Health Journal, 2026)
Background: Hospital healthcare services are required to produce positive outcomes, including reducing patient mortality rates. The Early Warning System (EWS) is used to detect early deterioration in patient conditions so that interventions can be administered more quickly. This study aims to analyze the factors associated with the accuracy of nurses’ EWS scoring and patient clinical outcomes at RSUD Mitra Sehat. Methods: This study was a quantitative study using an analytical observational design with a prospective cohort approach. Primary data were collected through questionnaires to analyze the effects of the King’s Interaction System and TOUS factors on the accuracy of nurses’ EWS scoring and their association with patient clinical outcomes at RSUD Mitra Sehat. Result: The results of the logistic regression test showed that the p-value for nurses’ knowledge was greater than the α value (0.05), at 0.220, with Exp(β) = 0.358. Nurses’ transactions had a p-value of 0.371, with Exp(β) = 2.116. These results indicate that both variables did not have a significant effect and were not statistically strong enough. Conclusion: Nevertheless, these factors still play a role. Patient clinical outcomes are more strongly influenced by underlying clinical conditions, comorbidities, disease severity, and limited medical resources, all of which can lead to delays in intervention.